Implementasi Just In Time System Dalam Meningkatkan Efisiensi Biaya Persediaan Bahan Baku - Selvi Indri Susanti; Khozin Arief (Indonesian Accounting Literacy Journal, 2021)
This study aims to look at the implementation of the Just In Time system in managing raw material inventory on inventory cost efficiency at the Much Desserts company. The research method used in this research is descriptive qualitative. Sources of data used are primary and secondary data sources with data collection techniques by observation, interviews, and documentation. From the results of research using the Just In Time system to control raw material inventory, it shows that there is an inventory cost efficiency of Rp3,646,429,- for raw materials for granulated sugar, whipping cream and milk with the percentage level of cost efficiency reaching 75%, 83,1%, and 75%.